Reator eletrônico auto-oscilante com alto fator de potência para alimentação de quatro lâmpadas fluorescentes independentes - Dalla Costa, Marco Antônio (2004)
This work describes a high-power-factor electronic ballast to supply four fluorescent lamps independently. Fluorescent lamp operational aspects are discussed, and a mathematical model to simulate the fluorescent lamp electric characteristics is proposed. This model, based on exponential approximation, is developed using experimental data. Multi-lamp arrangements are presented, and it is chosen the best arrangement for the proposed work. To choose the best valleyfill topology for passive power factor correction, theoretical and simulation analysis are included, chosen topology has to meet the IEC 61000-3-2 Class C requirements. A self-oscillating drive command modification is developed, in order to drive the switches independently of the converter load. Also, it is presented a simple circuit to correct the lamp current crest factor. Experimental results were obtained in order to validate the proposed work; these results were obtained for the ballast supplying four 32 W fluorescent lamps with switching frequency of 40 kHz, and line voltage of 220 Vrms.